2009
DOI: 10.1177/0956797609354734
|View full text |Cite
|
Sign up to set email alerts
|

Preverbal Infants’ Sensitivity to Synaesthetic Cross-Modality Correspondences

Abstract: Stimulation of one sensory modality can induce perceptual experiences in another modality that reflect synaesthetic correspondences among different dimensions of sensory experience. In visual-hearing synaesthesia, for example, higher pitched sounds induce visual images that are brighter, smaller, higher in space, and sharper than those induced by lower pitched sounds. Claims that neonatal perception is synaesthetic imply that such correspondences are an unlearned aspect of perception. To date, the youngest chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
296
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(332 citation statements)
references
References 27 publications
29
296
4
3
Order By: Relevance
“…Previous research also shows that three-month-old infants are able to discriminate sounds based on pitch [28] and four-monthold infants map non-rigid transformations of object thickness and rigid transformations of height to differences in pitch [32]. Further, studies using preferential looking (giving infants an option to look at two different screens) demonstrate that infants prefer to look at matched visual/acoustic events between the height and pitch of a moving object consistent with the Doppler effect [32,33], at pairings between object size and vowel type (high frontal vowels with higher F 0 and formants versus low posterior vowels with lowered F 0 and formants [34]) and at matches between pitch and the expansion and contraction of objects [35].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous research also shows that three-month-old infants are able to discriminate sounds based on pitch [28] and four-monthold infants map non-rigid transformations of object thickness and rigid transformations of height to differences in pitch [32]. Further, studies using preferential looking (giving infants an option to look at two different screens) demonstrate that infants prefer to look at matched visual/acoustic events between the height and pitch of a moving object consistent with the Doppler effect [32,33], at pairings between object size and vowel type (high frontal vowels with higher F 0 and formants versus low posterior vowels with lowered F 0 and formants [34]) and at matches between pitch and the expansion and contraction of objects [35].…”
Section: Introductionmentioning
confidence: 97%
“…That is, motion paired with emitted sounds may satisfy the input conditions of adaptations for picking up on invariant sound/object co-relations, irrespective of whether the object is a living thing vocalizing, or a non-living object producing noise [27][28][29][30][31][32][33][34]54]. However, because the acoustics produced by the living and non-living worlds are interestingly different from one another, both in terms of their properties and also in their affordances [9,16,22,23], the psychological mechanisms for representing and reasoning about the living versus the non-living worlds will likely become increasingly distinct from one another over the course of development.…”
Section: (A) Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The developmental trajectories of the discrimination of other quantities, such as loudness, pitch, pressure, temperature, density, motion, and saturation, have not been tested. However, there is evidence that young children and even infants can form compatible representations across many of these different dimensions (55)(56)(57)(58).…”
Section: For Review)mentioning
confidence: 99%
“…However, Ozturk et al [22] demonstrated that four-month-old children have a similar preference, indicating that substantial knowledge about language is not required in order to form these preferences. Similarly, Walker et al [23] showed that three-to four-month-old infants were able to form cross-modal correspondences between spatial height and angularity with auditory pitch, demonstrating that cross-modal correspondence preferences can precede substantial language learning rather than being a consequence of the fact that a particular language instantiates these correspondences [24].…”
Section: Introductionmentioning
confidence: 99%